A phase II study of cisplatin plus S-1 with concurrent thoracic radiotherapy for locally advanced non-small-cell lung cancer: The Okayama Lung Cancer Study Group Trial 0501. Issue 2 (February 2015) - Nogami, Naoyuki; Takigawa, Nagio; Hotta, Katsuyuki; Segawa, Yoshihiko; Kato, Yuka; Kozuki, Toshiyuki; Oze, Isao; Kishino, Daizo; Aoe, Keisuke; Ueoka, Hiroshi; Kuyama, Shoichi; Harita, Shingo; et al.
Highlights A S-1-based chemo-radiation was effective and safe in stage III NSCLC. The median progression-free survival time was 9.3 months. The median survival time was 31.3 months. Toxicities were generally mild except for febrile neutropenia and pneumonitis.